Assessment of Economic Efficiency Pertaining to Application of Energy Storage Units in Power System - A. M. Chernetsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
The paper considers some aspects pertaining to an application of technologies for energy storage in electric power. Review of technical and cost characteristics of energy storage units has been given in the paper. The review reflects data of the energy storage units which are available and which are under development. The paper proposes an approach that permits to assess boundaries of economically reasonable application of energy storage systems in order to balance daily load curve of a power system.